Multirate and Model Predictive Control of a Pneumatic Isolation Table with a Discrete Actuator. Issue 15 (2019) - Chida, Yuichi; Ishihara, Nijihiko; Tanemura, Masaya
Abstract: This study addresses the control problem for a pneumatic isolation table system that includes a discrete valued input actuator. Control performance occasionally deteriorates if it is impossible to use an adequate high sampling frequency for the system. A combined method of multirate control and model predictive control is proposed to improve control performance if the sampling frequency to measure outputs is insufficiently low. The effectiveness of the proposed method is verified via numerical simulations for a pneumatic isolation table system model.